"Who Wants to Know all this Stuff?!". (17th February 2022) - Alkhatib, Sami; Kelly, Ryan; Waycott, Jenny; Buchanan, George; Grobler, Marthie; Wang, Shuo
Abstract: The paper, '"Who Wants to Know all this Stuff?!": Understanding Older Adults' Privacy Concerns in Aged Care Monitoring Devices', by Sami Alkhatib, Ryan Kelly, Jenny Waycott, George Buchanan, Marthie Grobler and Shuo Wang, published in Interacting with Computers (November 2021), explores the use of care technology and the privacy concerns of older people.